Expression of Multidrug Resistance-Associated Protein 2 in Human Gallbladder Carcinoma. (16th June 2013) - Kim, Hyun-Soo; Kim, Nam Chul; Chae, Kyu Hee; Kim, Gun; Park, Won Seo; Park, Yong-Koo; Kim, Youn Wha
Abstract : Gallbladder carcinoma (GBCA) is one of the most aggressive malignancies. It is usually diagnosed at an advanced stage, and prognosis remains poor despite advances in imaging techniques and aggressive surgical treatment. Overexpression of multidrug resistance-associated proteins (MRPs) in tumor cells is a major cause of the intrinsic multidrug resistance phenotype. Despite the documented importance of MRP expression in many carcinomas, the prognostic significance of MRP2 expression in primary GBCA is not known. Immunostaining for MRP2 was performed on tissue samples obtained from 143 patients with GBCA. We examined the association between MRP expression and clinicopathological characteristics and outcome of patients with GBCA. GBCA demonstrated MRP2 immunoreactivity in the apicolateral membranes of epithelial cells. MRP2 expression was positive in 53.1% (76/143) of GBCA samples. Positive MRP2 expression was significantly associated with the presence of local recurrence (P = 0.038 ), lymphatic invasion (P = 0.038 ), vascular invasion (P = 0.023 ), and perineural invasion (P = 0.006 ). In addition, the median survival time of patients with MRP2-positive GBCA (15 months) was significantly shorter than that of patients with MRP2-negative GBCA (85 months, P = 0.011 ). We found that the expression of MRP2 in GBCA contributed to aggressive tumor behavior and poor prognosis, suggesting that MRP2 expression can be used as a potential prognostic biomarker of GBCA.